Peran lack of integrity sebagai pemodersi pengaruh fraud triangle terhadap pendeteksian fraudulent financial statement - Widjaya, Sri Dewi; Ari Minarwan; Satria Wibawa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to obtain empirical evidence of the influence of the Fraud Triangle element on the Fraudulent Financial Statement (FFS) for the 2018-2020 period with a Lack of Integrity (LoI) as moderating. Each element of the Fraud Triangle Model is calculated by proxying financial targets (ROA) for pressures, ineffective supervision (BDOUT) for opportunities, total accruals for rationalization, and real earnings management for Lack of Integrity. Then the FFS measurement uses the Beneish M-Score formula. The population in this study were banking companies listed on the Indonesia Stock Exchange during the period 2018 - 2020. The research sample was taken using a purposive sampling technique. The data used in this study is secondary data, namely in the form of audited company financial and annual reports and obtained through access to www.idx.co.id and/or the official website of each company. The data analysis method in this study uses panel data regression. The results of the study prove that Pressures and Opportunities do not have a positive effect on FFS. Rationalization has a positive effect on FFS. Lack of Integrity does not strengthen the positive influence of Pressures and Rationalization, but Lack of Integrity strengthens the positive influence of Opportunity on FFS.